Model-independent constraints on the hydrogen-ionizing emissivity at z > 6. Issue 2 (30th August 2019) - Mason, Charlotte A; Naidu, Rohan P; Tacchella, Sandro; Leja, Joel
ABSTRACT: Modelling reionization often requires significant assumptions about the properties of ionizing sources. Here, we infer the total output of hydrogen-ionizing photons (the ionizing emissivity, N_ion ) at z = 4–14 from current reionization constraints, being maximally agnostic to the properties of ionizing sources. We use a Bayesian analysis to fit for a non-parametric form of N_ion, allowing us to flexibly explore the entire prior volume. We infer a declining N_ion with redshift at z > 6, which can be used as a benchmark for reionization models. Model-independent reionization constraints from the cosmic microwave background (CMB) optical depth and Ly α and Ly β forest dark pixel fraction produce N_ion evolution ( d_10N_ion/ dz|_z=6→ 8 = -0.31± 0.35 dex) consistent with the declining UV luminosity density of galaxies, assuming constant ionizing photon escape fraction and efficiency. Including measurements from Ly α damping of galaxies and quasars produces a more rapid decline: d_10N_ion/ dz|_z=6→ 8 =-0.44± 0.22 dex, steeper than the declining galaxy luminosity density (if extrapolated beyond M_UV-13 ), and constrains the mid-point of reionization to z = 6.93 ± 0.14.